Locally connected nano-micro two-dimensional fillers in nanocomposites for advanced thermal management. (January 2020) - Li, Jialong; Yin, Jinghua; Liu, Xiaoxu; Zhao, He; Li, Yanpeng; Zhu, Congcong; Yue, Dong; Wang, Jimin; Feng, Yu; Su, Bo
Abstract: The co-filling of nano-sized 2D-BN pellets and micro-sized 2D-Ag sheets (AgMSs) (2 wt%) was used to improve thermal conductivity ( λ ) of PVDF-HFP-based composites. The nano-micro co-filled composites simultaneously possess high λ and excellent insulation properties. Compared with the sole-BN filled composites, high λ of the co-filled composites could be realized at relative low filler loading, and a maximal λ of 5.38 W m −1 K −1 is achieved in the PVDF-HFP/BN20/Ag2 composite. According to the detailed characterization results, a mechanism related to the construction of locally-connected structures, denser overall microstructure and reduced interfacial thermal resistance in the composites is proposed to be responsible for the enhanced λ and the excellent electrical insulating properties. Moreover, the finite element analysis (FEA) simulation results provide compelling evidence that the co-filled composites exhibit promising potential in thermal management applications. Consequently, this work provides a simple and effective method in fabricating superior thermal conductive yet insulating polymer-based composites.